Impacto das abordagens de convergência para as IFRS sobre a relevância das informações contábeis : uma análise nos países dos BRICS - Arrebola, Rafael (2024)
This research delves into the realm of emerging economies, specifically in the countries that make up BRICS - Brazil, Russia, India, China, and South Africa. In this context, the focus is on assessing the relevance of accounting information. During the analyzed period, these countries chose to adopt different approaches to comply with the International Financial Reporting Standards (IFRS). Thus, the central objective of this study is to examine how the convergence approach has impacted the relevance of financial information in these countries. To do so, the Ohlson methodology (1995) adapted by Collins et al. (1997) was employed to evaluate the market value relevance concerning profit and equity. The analysis is based on data from companies in these countries collected after the adoption of IFRS up to the year 2022. The impact of convergence approaches to IFRS on the relevance of accounting information was tested through cross-sectional regression analysis in the post-IFRS implementation periods in each country until the year 2022. The model is applied to each country, allowing comparisons between countries and groups that followed similar patterns in adopting the International Accounting Standards (IFRS). The central focus is to identify if there is evidence of uniform maturity in the relevance of accounting information over time among countries or groups with similar trajectories in converging to IFRS. However, the results challenged these expectations, revealing that the different approaches in implementing the standards did not clearly determine the evolution of informational value. The first hypothesis expected to observe discrepancies in the evolution of this relevance due to the different approaches in adopting IFRS. The second hypothesis predicted uniform patterns in the evolution of relevance among countries with similar approaches, while the third sought to identify similar patterns among countries with divergent standards. However, the data did not support these predictions, indicating that factors other than IFRS shaped the relationship between accounting information and market value. The research findings contribute to regulatory bodies promoting standards aimed at increasing the relevance of accounting information, as in most BRICS countries, relevance decreases after the adoption of IFRS. Investors, market analysts, and creditors should appropriately weigh the significance of accounting information in their analyses, given its declining relevance. The research also reveals that in the emerging markets of BRICS, convergence approaches to IFRS do not impact the relevance of accounting information. This motivates the academic community to explore other variables that may influence this relevance.